2016
DOI: 10.1097/aog.0000000000001506
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Preterm Birth and Early Term Birth

Abstract: OBJECTIVE To examine recurrent preterm birth and early term birth in women’s initial and immediately subsequent pregnancies. METHODS This retrospective cohort study included 163,889 women who delivered their first and second liveborn singleton neonates between 20 and 44 weeks of gestation in California from 2005 through 2011. Data from hospital discharge records and birth certificates were used for analyses. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using logistic regression models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 27 publications
7
60
0
1
Order By: Relevance
“…The strongest single predictor of both preterm and early-term delivery was a previous preterm birth (overall and by mode of onset of delivery), as confirmed in other population-based studies 31 32 and a recent systematic review which showed a 30% risk of recurrent sPTB following sPTB in singleton pregnancies. 33 In contrast, first-time mothers were more likely to deliver preterm, but not early term indicating that the shape of the risk distribution for early delivery in primiparae may slightly differ from the overall GA distribution which peaks around 38–40 weeks of gestation.…”
Section: Discussionsupporting
confidence: 63%
“…The strongest single predictor of both preterm and early-term delivery was a previous preterm birth (overall and by mode of onset of delivery), as confirmed in other population-based studies 31 32 and a recent systematic review which showed a 30% risk of recurrent sPTB following sPTB in singleton pregnancies. 33 In contrast, first-time mothers were more likely to deliver preterm, but not early term indicating that the shape of the risk distribution for early delivery in primiparae may slightly differ from the overall GA distribution which peaks around 38–40 weeks of gestation.…”
Section: Discussionsupporting
confidence: 63%
“…Our findings are consistent with these results: women with a spontaneous singleton early‐term birth are at greater risk of PTB in a subsequent twin pregnancy than are women with a prior full‐ or late‐term birth, and this association persisted after adjustment for potential confounders. Our data and those of Yang et al show that the dichotomy between previous preterm and term birth is artificial for the risk of subsequent PTB: the risk is a continuum, and the lowest risk is observed only among women with a previous full‐ or late‐term birth.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, this higher risk exists after both spontaneous and indicated PTBs . Yang et al recently reported that a shorter gestational duration in the first singleton pregnancy increases the risk of subsequent singleton PTB and early‐term birth; in particular, women with a prior early‐term birth are at higher risk of subsequent PTB than are women with a prior full‐ or late‐term birth. Our findings are consistent with these results: women with a spontaneous singleton early‐term birth are at greater risk of PTB in a subsequent twin pregnancy than are women with a prior full‐ or late‐term birth, and this association persisted after adjustment for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…It will also be important to examine how this test behaves in identifying pregnancies that deliver early term (37 and 38 weeks). Given mounting data demonstrating that early term babies are at increased risk for both short- and long-term morbidity [ 47 ] and that these women are more likely to deliver preterm in the next pregnancy [ 48 ] it would be advantageous to be able to identify these women early in pregnancy in an effort to extend gestation.…”
Section: Discussionmentioning
confidence: 99%